Answer:
1) The values of 'a' and 'b' are
and
respectively.
2) The values of 'a' and 'b' are '3' and '-3' respectively.
Explanation:
1) Given:
![$ (3x)/((x - 2)(3x + 2)) = (a)/(x - 2) + (b)/(3x + 2) $](https://img.qammunity.org/2020/formulas/mathematics/middle-school/ghjderwjod74if3btqchbqrfuft8x4ejo0.png)
We solve this by partial fraction method.
Taking LCM in the RHS we get,
![$ (3x)/((x - 2)(3x + 2)) = (a(3x + 2) + b(x - 2))/((x - 2)(3x + 2)) $](https://img.qammunity.org/2020/formulas/mathematics/middle-school/t3sypjfv6lu2gga35od95kcsbhk88c1n85.png)
![$ \implies 3x = a(3x + 2) + b(x - 2) $](https://img.qammunity.org/2020/formulas/mathematics/middle-school/2clok1gr6dhx3k7exl9bnlu25h563r0ot7.png)
To find the value of 'a', substitute x = 2. This would make 'b' vanish leaving an equation with 'a'.
![$ \therefore 3(2) = a(3.2 + 2) + b (2 - 2) \implies 6 = a(8) $](https://img.qammunity.org/2020/formulas/mathematics/middle-school/q0jb2j46bav5794pqe5173i2lo8v8d9mtu.png)
![$ \implies a = (-2)/(3) $](https://img.qammunity.org/2020/formulas/mathematics/middle-school/341xce7vawhdkhsrhw0urd3emd3f1ovbd8.png)
Now, Substitute
to solve for 'b'.
![$ \implies 3((-2)/(3)) = a (3.(-2)/(3) + 2) + b((-2)/(3) -2) $](https://img.qammunity.org/2020/formulas/mathematics/middle-school/ajjw74zs6s6j6foifec2c2ppjeml58hnti.png)
![$ \implies -2 = b (-8)/(3) $](https://img.qammunity.org/2020/formulas/mathematics/middle-school/6tvfezjgz8ixyz02sq7qywnlsef30hg55y.png)
![$ \implies b = (3)/(4) $](https://img.qammunity.org/2020/formulas/mathematics/middle-school/mqlas4corkx9uff6fwyauhu55032aedh5t.png)
Therefore, a =
and b =
![$ (3)/(4) $](https://img.qammunity.org/2020/formulas/mathematics/college/97psq3ks9im2e1ysdgsljl5xxaqapdkltz.png)
2) Given
![$ (3)/(x^2 - 5x + 6) = (a)/(x - 2) + (b)/(x - 3) $](https://img.qammunity.org/2020/formulas/mathematics/middle-school/m3wmtxrg1c80ng6zcspq3jh8nf7w26wbga.png)
We follow the same procedure as (1).
Taking LCM we get
![$ (3)/(x^2 - 5x + 6) = (a (x - 3) + b(x - 2))/((x^2 - 5x + 6)) $](https://img.qammunity.org/2020/formulas/mathematics/middle-school/cdfld0q7uze6ro6jqhep14oezx9gvy9els.png)
![$ \implies 3 = a(x - 3) + b(x - 2) $](https://img.qammunity.org/2020/formulas/mathematics/middle-school/prl14tx9bwch8p6di1kl22cvz3wpm2o2mt.png)
Substituting x = 2, we get:
3 = a(-1)
![$ \implies a = -3 $](https://img.qammunity.org/2020/formulas/mathematics/middle-school/953fxsc4gd5tcqpoq2g5ybes17q4u2e60d.png)
Also, Substituting x = 3, we get:
3 = b(1)
![$ \implies b = 1 $](https://img.qammunity.org/2020/formulas/mathematics/middle-school/hw6m8i76zm2jku88j60491wz5pqag8kzau.png)
Therefore, the values of a and b are -1 and 1 respectively.